Monitoring Kesehatan Warga Desa Sidodadi Ramunia Melalui Pemberdayaan Kader Posyandu Berbasis Cloud Computing - Sindar Sinaga, Anita; Panggabean, Erwin; Mulyani, Sri (LPPM Universitas HKBP Nommensen, 2024)
Empowering village residents requires support from network infrastructure and devices, software, digital literacy and assistance. Posyandu plays a role in helping the Village Government (Pemdes) improve basic health and social services. Problems that arise are that Posyandu cadres. IT skills need to be trained so that reporting from the field can be directly connected to village reports. The solutions provided through PKM activities are increasing the participation of mothers and toddlers, the elderly in posyandu and increasing the IT skills of Posyandu cadres. Community empowerment activities produce digital applications. during eight months service activity resulted in a health monitoring application system aimed at facilitating monitoring of posyandu activities in Ramunia Village.